Catalytic pyrolysis of biomass over zeolites for bio-oil and chemical production: A review on their structure, porosity and acidity co-relation. (December 2022) - Mishra, Ranjeet Kumar; Chistie, Syeda Minnat; Naika, Sneha Ullhas; Mohanty, Kaustubha
Graphical abstract: Highlights: The shape selectivity of ZSM-5 has been addressed in order to improve bio-oil quality. ZSM-5′s catalytic activity, structure, and surface chemistry have all been spotlighted. The acidity of the ZSM-5 catalyst has been thoroughly investigated. The process characteristics of ZSM-5 catalysts have been described. Abstract: The oxygenated compounds found in bio-oil limit their application as a transportation fuel. Several studies were reported on eliminating the oxygenated components from bio-oil so as to improve its fuel properties. This work is dedicated to studying the shape selectivity, porosity, structure, acidity of zeolites and their effect in bio-oil and chemicals production. The unified pore size, specific structure, controlled Si/Al ratio, unique channels and circular entrances, mesoporosity, and acidity are the utmost discerning parameters for aromatics production and deoxygenation reaction. The conversion of biomass-derived oxygenates to aromatics using zeolite is subjected to the reactants entering the pore, conversion inside the pore, and diffusing out of the products from the zeolite pores. These approaches were considered for an in-depth understanding of zeolite properties, which will enhance the fundamental understanding of pyrolysis.